User Interface Design With User Centered Design (UCD) Method on Bread Sales Mobile Application PT.Nippon Indosari Corpindo, Tbk - Salsa Salsa Az-zahra; Irsan Jaelani; Lise Sri Andar Muni (RISTEC : Research in Information Systems and Technology, 2021)
PT. Nippon Indosari Corpindo,Tbk. is one of the companies engaged in the food industry with its flagship product, namely bread with the brand "SARI ROTI". PT Nippon Indosari Corpindo,Tbk has been established since 1995. At PT Nippon Indosari Corpindo,Tbk, according to the author, the online buying and selling system used is not yet effective and efficient, because customers have to click the link to whatsapp to order, if the order has been entered then from the agent The center provides information to the nearest agent according to the location of the order ordered by the customer, and afterthat the nearest agent canonly send the order. Therefore, there is a lack of efficiency in the purchasing system. The problem isthat it does not yet have a prototype user interface for the Sari Roti mobile application. Based on these problems, user interface design was carried out and produced a prototype of the Sari Roti mobile application using a user centered design (UCD) model and for evaluation of the initial design using a usability scale (SUS) system to 11 respondents. This research is successful in designing a user interface that can view product lists, product details, make transactions, and order status. The initial design evaluation uses a usability scale system with initial calculations showing an average valueof 82,withGrade B